Management of tourism and recreation possibilities for the sustainable development of the north-western border region in Russia - Dmitry V. Sevastiyanov; Alfred Colpaert; Eugene Korostelyov; Oleg Mulyava; Larissa Shitova (The Geographical Society of Northern Finland, 2014)
This article gives an overview of the present and future possibilities for the development of tourism and recreation in North-West Russia. This area has substantial number large federal and national parks, especially the size of these protected areas differentiates them clearly from the network of protected areas in western Europe, also their northern and Arctic location in the last wilderness of Europe provides many opportunities for eco-tourism, nature recreation for both Russians and the international public. The so called Green Belt of Scandinavia, running north - south from the Arctic Sea along the border between Norway, Finland and Russia provides many opportunities to increase cross border tourism and in the same time improve the protection status of these areas. To benefit from these opportunities local infrastructure has to be improved, but this rising economic sector, e.g. the tourism industry might be of paramount importance to local and regional economies, and possibly to the whole of the Russian Federation.